Ekstraksi Natrium Silikat dengan NaOH pada Abu Sekam Padi dari Limbah Pertanian di Kecamatan Gedangan, Jawa Timur, dan Kuantifikasi Kadar Silikanya dengan Metode Spektrofotometri Molybdenum Biru - Kariza Alya Aulia Firdaus; Amaria (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
Rice husk is an agricultural waste with potential as a silica source due to its high silica content after ashing. This study aimed to quantitatively determine the silica content in NaOH extract of rice husk ash obtained from agricultural waste in Gedangan District, East Java, using the molybdenum blue spectrophotometric method. The rice husk was washed, dried, ashed at 700 ℃ for 4 h, and sieved to pass 200 mesh. Silica extraction was carried out through acid leaching with HCl, chelation with Na2EDTA, and dissolution using 3.5 M NaOH under reflux for 1 h to produce sodium silicate solution. Silica content was determined by UV-Vis spectrophotometry at 810 nm using a silica standard curve of 0.2–1.8 mg/L. The ashing process yielded an average ash yield of 21.18% with 0.72% RSD, indicating good consistency. The silica analysis of the extract showed average values of 1482.30 mg/L for sample 1 and 1133.09 mg/L for sample 2. These results indicate that rice husk ash from Gedangan District, East Java, has potential as a source of dissolved silica through alkaline extraction.